Bionomics of black flies (Diptera: Simuliidae) in Costa Rica. VII. Genus Simulium subgenus Hearlea - Vargas V., Mario; Travis, B. V.; Díaz Nájera, A.; Fallas B., F. (Revista de Biología Tropical, 1977)
Black fly populations were studied in 100 streams in Costa Rica for a period of two years. Among the specimens collected in the field were larvae and pupae of the subgenus Hearlea. A comparison of available material from Canada, Mexico, Guatemala and Panama allowed us to identify the species of Hearlea as Simulium (Hearlea) chiriquiense Field, 1967. This is the first report of this subgenus and species for this country; distribution and other ecological data are presented.